Experimental Shakedown Analysis of Space Truss Nodes - J.A. Karczewski; J.A. Konig (Engineering Transactions)
The purpose of the paper is to discuss the problem of the behaviour of the space truss node subjected to alternating loading greater than the maximum load carrying capacity in the elastic range. A certain experimental method is proposed which allows to investigate the plastic strain stabilization process. The results of shakedown investigations of full-size nodes composed of fiat plates seem to confirm the practical applicability of the above method. During the experiment the strain variations were recorded with the help of strain gauges and photoelastic coating made of synthetic resin epidian 2.